Relations between baseline burden, maximum duration, and relative reduction of atrial fibrillation: Insights from continuous monitoring in rhythm control - Lin, Po‐Lin; Huang, Chun‐Che; Wu, Yih‐Jer; Su, Min‐I; Chiou, Wei‐Ru; Liu, Lawrence Yu‐Min; Liao, Feng‐Ching; Lai, Edward; Chen, Chun‐Yen; Kuo, Jen‐Yuan; Lee, Ying‐Hsiang (Journal of cardiovascular electrophysiology, 2019)
Introduction Cardiac implantable electronic devices (CIEDs) can measure atrial fibrillation (AF) early; however, the timing for administering antiarrhythmic drugs (AADs) to suppress AF remains unclear. This study aimed to investigate the association between baseline values and changes after AAD in terms of relative reduction of AF burden (RRAB) and maximum AF duration (RRMD). Methods This multicenter retrospective study screened all patients with nonpermanent AF who had dual‐chamber pacemakers and only enrolled those receiving a naive AAD between September 2009 and December 2014. AF burden and maximum duration were calculated using CIED at 0 and 3 to 6 months after starting rhythm control. All the enrolled patients were divided into four groups according to baseline AF burden. RRAB and RRMD were monitored using CIEDs. Results Overall, 145 eligible subjects received a naive AAD for nonpermanent AF. The mean RRAB in the four groups (AF burden <1%, 1%‐4%, 4%‐18%, and ≥18%) were −65.3%, −46.4%, −34.7%, and −27.9% (P = 0.005), respectively. Mean RRMD were −26.8%, −12.4%, 4.2%, and 6.0%, respectively ( P = 0.006). Multivariate analysis revealed that the lowest baseline AF burden (<1%) was significantly associated with greater RRAB, which was not observed in the RRMD model. Conclusions Lower baseline AF burden was associated with greater RRAB by AADs. Our finding suggests that rhythm control should be started in the early stage to achieve better responses to AADs.